2002
DOI: 10.1080/10473220290035705
|View full text |Cite
|
Sign up to set email alerts
|

Diisocyanate Emission from a Paint Product: A Preliminary Analysis

Abstract: Exposure of workers to diisocyanates in the polyurethane foam manufacturing industry is well documented. However, very little quantitative data have been published on exposure to diisocyanates from the use of paints and coatings. The purpose of this study was to evaluate emission of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate (2,6-TDI), and isophorone diisocyanate from a commercially available two-stage concrete coating and sealant. A laboratory model of an outdoor deck coating process was developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…These analyses should include (1) measurement of amount of diamine/mole HSA following acid hydrolysis, (2) TNBS measurement of cross-linking, (3) denature gel electrophoresis for indication of intermolecular and intra-molecular cross-linking, and (4) use of mAb for antigenicity standardization. Both qualitative and quantitative differences in MDI binding were observed between Hb and HSA conjugates suggesting normalization to conjugation ratio is not sufficient to compare antigenicity of different diisocyante haptenated proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These analyses should include (1) measurement of amount of diamine/mole HSA following acid hydrolysis, (2) TNBS measurement of cross-linking, (3) denature gel electrophoresis for indication of intermolecular and intra-molecular cross-linking, and (4) use of mAb for antigenicity standardization. Both qualitative and quantitative differences in MDI binding were observed between Hb and HSA conjugates suggesting normalization to conjugation ratio is not sufficient to compare antigenicity of different diisocyante haptenated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to dNCO has most commonly been reported in the occupational setting (3;4); however, concern of potential exposure through leaching of dNCOs from cured, semi-cured or non-cured products has recently been raised in domestic settings(5). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their role in development of non‐occupational asthma is not entirely clear. However, emission of isocyanate ceased within 5 h after the application of an isocyanate paint (Jarand et al., 2002) and emission also had a fast decay of isocyanates from polyurethane adhesives (Wirts and Salthammer, 2002), which suggests mainly occupational exposures. Overall, few VOCs have been identified as allergenic (Becher et al., 1996).…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%
“…The annual production of isocyanates worldwide was about 4.4 million metric tons in 2002 4 and, currently, an estimated 440,000 workers are exposed to isocyanates in the United States 5 – 7 . Exposures in the general population can occur from contact with isocyanate-containing consumer goods (e.g., Gorilla glue ® ), slow-curing isocyanate coatings, materials used in housing construction, in outdoor areas near industrial sites where isocyanates are used in manufacturing, or in neighborhoods surrounding auto-refinishing businesses 8 10 . While inhalation exposure to isocyanates has been considered the most important route through which allergic sensitization may occur, animal studies have shown that skin exposure can result in respiratory sensitization 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%